How does “race” matter in Switzerland ? - Lavanchy Leviqueo Painemil, Anne (My University, 2014)
This essay explores the institutional production of “desirable nationals” through administrative procedures of marriage and civil partnership in Switzerland. Borrowing from the field of critical race studies, it focuses on bureaucratic practices related to unions – marriages and civil partnerships – to analyse the tensions around the (re)production of an idealized Swissness”.
The argument presented herein has a dual purpose: on an epistemological and theoretical level, it first exposes why critical race studies offer an appropriate vantage point from which to analyze how Swiss society is structured by unspoken racialised categorizations. Its second purpose is to shed light on institutional technologies of protection of the national body in registry offices. With the development of bureaucratic technology aiming at tracking down “sham marriages”, the work of registrars is increasingly about the selection of potential co-nationals. This piece shows how the rhetoric of good marriages/civil partnerships is linked to narratives about “homogamy” and “mixedness”, framing racialised understandings of nationality.
Keywords: Nationality; Critical race studies; Marriage & civil partnerships; Institutions